Performance validity testing in children and adolescents: A descriptive study comparing direct and embedded measures. Issue 2 (3rd April 2019) - Weiss, Stephanie J.; Blackwell, Melissa C.; Griffith, Kirk M.; Jordan, Leslie S.; Culotta, Vincent P.
ABSTRACT: Effort testing is a standard element in adult neuropsychological assessment. Research examining performance validity tests (PVTs) has focused on adults. The purpose of this descriptive study was to examine direct and embedded PVTs in children and adolescents. The Test of Memory Malingering (TOMM), a stand-alone PVT, was compared to two embedded measures of effort: California Verbal Learning Test-Children's Version/Second Edition (CVLT-C/II) Recognition Discriminability and Reliable Digit Span (RDS). The sample consisted of 119 children and adolescents referred for outpatient assessment. Cut-off scores used for PVTs were based on previous studies. Results revealed 3/119 failures on the TOMM, 14/119 failures on the RDS, and 34/119 failures on the CVLT-C/II. There was a significant difference between failures on the TOMM and the RDS, as well as between failures on the TOMM and the CVLT-C/II and the RDS and the CVLT-C/II. The results of this study demonstrate that PVTs commonly used with adults may require modifications, including adjusted cut-off scores, to be appropriate with children and adolescents. Results of this study also suggest that relying on more than one measure likely provides the most utility.